1994
DOI: 10.1029/94jb01186
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Kuril Trench from seismic reflection records

Abstract: Three multichannel seismic reflection records across the Kuril convergent margin provide the first deep data in this area. The records are located across the southern tip of Kamchatka, the central Kuril arc, and the northern extension of Hokkaido Island platform which show three distinct tectonic regimes. The lower slope contains a wedge‐shaped buttress surrounded by low velocity sediments. Underplating sediment uplifts the buttress, as indicated by faults that displace its upper surface. The middle slope is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…Five of them are consistent with thrust motion along fault planes that strike nearly orthogonal to the nearby trench (Suzuki et al, 1983;Seno, 1985). Furthermore, three earthquakes, labelled by De Mets: 6, 25 and 26, are located closer to the trench axis and may indicate that the shear induced by oblique subduction is distributed along two or more subparallel strikeslip faults in the forearc (De Mets, 1992;Klaeschen et al, 1994). Earthquake 26 is located just at the northern edge of line P-856 and supports the hypothesis of a trench-parallel, strikeslip fault cutting the section at the edge of the continental terrace (km 72).…”
Section: Discussionmentioning
confidence: 74%
“…Five of them are consistent with thrust motion along fault planes that strike nearly orthogonal to the nearby trench (Suzuki et al, 1983;Seno, 1985). Furthermore, three earthquakes, labelled by De Mets: 6, 25 and 26, are located closer to the trench axis and may indicate that the shear induced by oblique subduction is distributed along two or more subparallel strikeslip faults in the forearc (De Mets, 1992;Klaeschen et al, 1994). Earthquake 26 is located just at the northern edge of line P-856 and supports the hypothesis of a trench-parallel, strikeslip fault cutting the section at the edge of the continental terrace (km 72).…”
Section: Discussionmentioning
confidence: 74%
“…2 and 5). The upper terrace is underlain by wellstratifi ed refl ectors (Schnürle et al, 1995;TuZino et al, 2006) and possibly formed via a combination of subsidence and regional tilting (Klaeschen et al, 1994). TuZino et al (2006) reported the formation of half-grabens along the upper terrace Table DR2).…”
Section: Coastal and Submarine Areasmentioning
confidence: 96%
“…Clift et al, 1998;Dickinson and Seely, 1979;Gulick et al, 2002;McNeill et al, 2000). The high can be correlated with the middle-slope boundary of a steep landward-dipping refl ection described by Klaeschen et al (1994). Two terraces are recognized on the slope: the upper terrace (3200 m water depth) is located on the upper slope immediately behind the outer high, and the lower is located on the trenchward side of the outer high (5000-5500 m water depth) (Figs.…”
Section: Coastal and Submarine Areasmentioning
confidence: 97%
See 1 more Smart Citation
“…The lower slope is bounded by the outer high that consists of non-layered acoustic basements ( Fig. 5B and C) (Honza et al, 1978;Klaeschen et al, 1994;Schnürle et al, 1995). The sediments of the lower slope represent the formation of a half-graben, suggesting Fig.…”
Section: Seismic Profilesmentioning
confidence: 97%